In-Situ Preparation of CdTe Quantum Dots Capped with a β-Cyclodextrin-Epichlorohydrin Polymer: Polymer Influence on the Nanocrystal’s Optical Properties - Rudy Martin-Trasanco; Hilda E. Esparza-Ponce; Pedro D. Ortiz; Diego P. Oyarzun; Cesar Zuñiga; Maria E. Montero-Cabrera; Alain Tundidor-Camba; Guadalupe del C. Pizarro; Ramiro Arratia-Pérez (Nanomaterials, 2018)
β-Cyclodextrin (βCD), the less water soluble of the cyclodextrins, has been used as a capping agent in the preparation of semiconductor nanocrystals or quantum dots (QDs). Nevertheless, no reports have been found in the use of the highly water-soluble polymer of this, prepared by the crosslinking of the βCD units with epichlorohydrin in basic medium (βCDP). This polymer, besides to overcome the low solubility of the βCD, increases the inclusion constant of the guest; two parameters that deserve its use as capping agent, instead of the native cyclodextrin. In the present manuscript, we afforded the in-situ aqueous preparation of cadmium telluride (CdTe) QDs capped with βCDP. The polymer influence on the photoluminescent properties of the nanocrystals was analyzed. The βCDP controls the nanocrystals growth during the Oswald ripening stage. Consequently, the CdTe capped βCDP QDs showed lower Stokes-shift values, higher photoluminescent efficiency, and narrower size distribution than for nanocrystals obtained in the absence of polymer. Transmission electron microscopy (TEM) micrographs and energy dispersive X-ray spectroscopy (EDS) analysis revealed the composition and crystallinity of the CdTe QDs. This βCDP capped CdTe QDs is a potential scaffold for the supramolecular modification of QDs surface.